The impact of multiple chronic diseases on ambulatory care use; a population based study in Ontario, Canada - Muggah Elizabeth; Graves Erin; Bennett Carol; Manuel Douglas G (BMC, 2012)
Abstract Background The prevalence of multiple chronic diseases is increasing and is a common problem for primary health care providers. This study sought to determine the patient and health system burden of multiple chronic diseases among adults in Ontario, Canada, with a focus on the ambulatory health care system (outpatient primary health care and specialist services). Methods This population-based study used linked health administrative data from Ontario, Canada. Individuals, aged 20 years or older, who had a valid health card, were included. Validated case definitions were used to identify persons with at least one of the following nine chronic diseases: diabetes, congestive heart failure, acute myocardial infarction, stroke, hypertension, asthma, chronic obstructive lung disease, peripheral vascular disease and end stage renal failure. Prevalence estimates for chronic diseases were calculated for April 1, 2009. Ambulatory physician billing records for the two-year period, April 1, 2008 to March 31, 2010, were used to identify the number of outpatient ambulatory care visits. Results In 2009, 26.3% of Ontarians had one chronic disease, 10.3% had two diseases, and 5.6% had three or more diseases. Annual mean primary health care use increased significantly with each additional chronic disease. Overall, there were twice as many patient visits to primary health care providers compared to specialists across all chronic disease counts. Among those with multiple diseases, primary health care visits increased with advancing age, while specialist care dropped off. While persons with three or more diseases accounted for a disproportionate share of primary health care visits, the largest number of visits were made by those with no or one chronic disease. Conclusions The burden of care for persons with multiple chronic diseases is considerable and falls largely on the primary health care provider. However persons with no or one chronic disease are responsible for the largest number of ambulatory health care visits overall. Continued investment in primary health care is needed both to care for those with multiple diseases and to prevent the accumulation of chronic diseases with aging.